Mental illness as a social problem in the Philippines during the Spanish colonial period - Paular, Regino P. ([Metro Manila] Psychological Association of the Philippines, 1992)
Examined the contents of archival materials and other available Spanish documents for the purpose of analyzing data on mental illness in the Philippines, particularly during the 19th century (the latter part of the Spanish regime). The material indicates that during the 19th century, the Philippines, through Spain, had already established an insane asylum in Manila, as well as medical supervision of the Hospicio de San Jose; from 1865 to 1898, 741 mentally disturbed Ss were diagnosed, admitted, and treated there. The mentally disturbed Ss were subjected to psychomedical examination before admission and the government physician acted as the sole authority on diagnoses and the consequent recommendation. There were many psychopathological terms that show a considerable European influence, and some of these terms are still commonly used today. There existed certain cases labeled as insane for social and political reasons.
Includes bibliographical references(pages 18-19)
Keywords: Psychology Philippines -- Periodicals